Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Matematika Menggunakan Kombinasi Model Pembelajaran Problem Based Learning, Group Investigation dan Make A Match Pada Siswa Kelas IV SDN Sungai Miai 4 - Hairunnisa; Radiansyah (CV. ITTC INDONESIA, 2024)
The classroom action research conducted in class IV of SDN Sungai Miai 4 occurred due to problems in the form of low student activity and learning outcomes in mathematics lessons. This problem occurs due to monotonous learning so that students' critical thinking skills do not develop. This classroom action research was conducted in three meetings in class IV of SDN Sungai Miai 4 in the even semester of the 2023/2024 academic year with all 22 class IV students as research subjects. It can be seen from the results of the study that there has been an increase in all aspects studied. Teacher activity becomes